The Costs of Treating American Indian Adults With Diabetes Within the Indian Health Service - O'Connell, Joan M. (American Public Health Association, 2012)
Objectives. We examined the costs of treating American Indian adults with diabetes within the Indian Health Service (IHS). Methods. We extracted demographic and health service utilization data from the IHS electronic medical reporting system for 32 052 American Indian adults in central Arizona in 2004 and 2005. We derived treatment cost estimates from an IHS facility–specific cost report. We examined chronic condition prevalence, medical service utilization, and treatment costs for American Indians with and without diabetes. Results. IHS treatment costs for the 10.9% of American Indian adults with diabetes accounted for 37.0% of all adult treatment costs. Persons with diabetes accounted for nearly half of all hospital days (excluding days for obstetrical care). Hospital inpatient service costs for those with diabetes accounted for 32.2% of all costs. Conclusions. In this first study of treatment costs within the IHS, costs for American Indians with diabetes were found to consume a significant proportion of IHS resources. The findings give federal agencies and tribes critical information for resource allocation and policy formulation to reduce and eventually eliminate diabetes-related disparities between American Indians and Alaska Natives and other racial/ethnic populations.